Is There Moral Hazard in Islamic Rural Bank Financing? - Oktarina, Adelia; Fahmi, Idqan; Beik, Irfan Syauqi (IQTISHADIA, 2019)
The credit market was identical to asymmetric information in it, both conventional and sharia credit markets. One of the forms of this asymmetric information was moral hazard. This study aimed to identify the existence of moral hazard in credit market (financing) by comparing the customer conditions in islamic rural bank and conventional rural bank. This study also intended to identify the factors influencing the moral hazard. The analysis used was logistic regression method. The result showed that islamic rural bank had a bigger potential to experience moral hazard compared to the conventional customers. Generally, the factors which influence the moral hazard such as age, business conditions, amount of financing, length of financing, and type of bank.